The Coming Out of Advertising: Bulakeño Millennials' and Generation Z Responses to Homosexual-Themed Advertisements - Blas, Allyana Denise; Dela Cruz, Chayra Fiel; Dela Rosa, John Benedict; Guiao, Analyn; Valencia, Beverly; Tan, Jian Carlo (Future Science / FSH-PH Publications, 2025)
Homosexual imagery in advertising has increased in recent years, reflecting greater inclusivity and diversity in marketing. Even though such campaigns gained global attention, reactions differed across cultural contexts. This study explored Filipino consumers' tolerance of homosexuality and its impact on responses to homosexual-themed advertising and brand attitude. It also examined how developmental factors, traditional culture, and generational differences influenced homosexual tolerance. Through a quantitative approach, data from 403 participants were gathered via an online survey. The researchers analyzed variable correlations using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results revealed that a higher tolerance of homosexuality correlated with a more positive attitude toward such advertisements and brands. Furthermore, developmental factors and generational differences positively influenced homosexual tolerance, whereas traditional culture had a negative impact. Understanding these factors provided insights for advertisers and marketers on inclusive campaigns that resonated with diverse audiences and laid a foundation for future research.